BaTiO3/Epoxy Resin Nanocomposites as Flexible Energy Storage Devices - Vittayakorn, Wanwilai; Tepsansern, Piyapat; Kriangkraikul, Worachet; Vittayakorn, Naratip (My University, 2023)
In this work, nanocomposites between the epoxy resin and barium titanate (BT) were prepared in order to use as flexible energy storage devices. The epoxy resin and BT phase were homogeneously mixed and cast into a disk shape. Phase formation and chemical properties of these nanocomposites were identified via XRD and FTIR methods, respectively. Frequency dependence of dielectric properties for all samples was measured by LCR meter. The polarization hysteresis loops were also investigated in order to calculate the energy density of materials. From the results, it was found that the dielectric constant and loss of these nanocomposites are independent of frequency and the εr and tanδ values tend to increase with increasing BT amount. Moreover, after adding 50% of BT into the system, the energy density of nanocomposites is increased by five times compared with the pure epoxy resin while the energy loss density sharply decreases. The dielectric properties and the energy density of BT/epoxy resin nanocomposites change with BT content and strongly depend on porosity and the distribution of BT nanoparticles.
Keywords: barium titanate; energy storage; Epoxy resin; nanocomposite